Proposed upgrading of Universiti Teknologi MARA (UiTM) Facility Management Office (BPF) for Universiti Teknologi MARA (UiTM), UiTM Perak at Universiti Teknologi MARA (UiTM) Facility Management Department, Perak / Nur Madihah Marzuki - Marzuki, Nur Madihah (Faculty of Architecture, Planning and Surveying, 2012)
This final project is materialization and verification of the Interior Design student’s knowledge for 3 years of learning about interior design from the fundamentals to all aspect of Interior Design course. The proposed final project is Upgrading of Universiti Teknologi Mara Perak Facility Management Office For Universiti Teknologi MARA (UiTM) Perak at Universiti Teknologi MARA Perak Facility materialization Management Division For Universiti Teknologi MARA . The purpose of this project is to proposed upgrading to a higher standard, in particular to improve (equipment and interior) by adding or replacing components, structures, fixtures, furnitures, etc. of Facility Management Office At Universiti Teknologi MARA (UiTM), Perak. Facilities Management Office (BPF) is a support service organization that has been responsible for strengthening service delivery systems, the maintenance of university facilities, the development of teaching learning and competitiveness can be improved in line with UiTM's mission to become a learning institution High winner. Basically, Facility Management is like the main or nerve of of the whole UiTM because any building projects development and maintenance has to go through BPF before any development or maintenance to buildings are made.